PROJECTION OF THALASSEMICS IN KHYBER PAKHTUNKHWA - Wazir, Saima; Zaheer, Zafar (Journal of Postgraduate Medical Institute, 2016)
Objective: To predict the number of thalassemics in Khyber Pakhtunkhwa. Methodology: In the first step, of estimating the patients and carriers of the disease, population projection is done with cohort component method of analysis. Pakistan Demographic Surveys conducted by Pakistan Bureau of Statistics was used to collect the data for projection of the total population. Then the output of population projection was used to analyze the number of thalassemics in the total population. Hardy-Weinberg Analysis, a technique adopted from genetics, was used to identify the number of thalassemia major and thalassemia minor patients in the population. Results: There are an expected number of 647 children with thalassemia major each year. Similarly, 35,054 individuals will be added to the population, each year, which may carry thalassemia genes. Conclusion: With the increasing population the number of thalassemia affected individuals is increasing in the region.